Long-Term Effect of Semaglutide on the Glomerular Filtration Rate Slope in High-Risk Patients with Diabetic Nephropathy: Analysis in Real-World Clinical Practice - Enrique Luna; Álvaro Álvarez; Jorge Rodriguez-Sabiñón; Juan Villa; Teresa Giraldo; Maria Victoria Martín; Eva Vázquez; Noemi Fernández; Belén Ruiz; Guadalupe Garcia-Pino; Coral Martínez; Lilia Azevedo; et al. (Pharmaceutics)
Background: Semaglutide, a GLP-1 receptor agonist, has shown promising nephroprotective effects in clinical trials, though real-world data on its long-term impact on renal function in high-risk diabetic nephropathy patients remain scarce. Methods: We conducted a multicenter, retrospective observational study involving 156 patients with type 2 diabetes and chronic kidney disease (CKD) treated with subcutaneous semaglutide between 2019 and 2023. Inclusion required an eGFR > 15 mL/min/1.73 m2 or albuminuria > 30 mg/g and at least two years of follow-up. The primary outcome was the change in eGFR slope after semaglutide initiation. Subgroup analyses were performed based on baseline eGFR, albuminuria, and SGLT2i co-treatment. Results: In the whole study population, the median eGFR slope significantly improved from −3.29 (IQR 7.54) to −0.79 (IQR 6.01) mL/min/1.73 m2/year post-treatment (p < 0.001). Multiple linear regression showed a hazard ratio for the effect of semaglutide on the eGFR slope of 4.06 (2.43–5.68), p < 0.001. In patients with baseline eGFR < 60 mL/min/1.73 m2, the slope improved from −3.77 to −1.01 (p < 0.0001), while patients on concurrent SGLT2i therapy saw slope changes from −2.96 to −0.37 (p < 0.0001). Patients with albuminuria 30–1000 mg/g also improved from −2.96 to −0.04 (p < 0.0001); however, those > 1000 mg/g did not show a significant change (p = 0.184). Semaglutide also reduced BMI (p = 0.04), HbA1c (p = 0.002), triglycerides (p = 0.001), CRP (p = 0.003), and GGT values (p = 0.004). Conclusions: In real-world practice, semaglutide significantly attenuated renal function decline in high-risk diabetic patients, particularly those with advanced CKD or concurrent SGLT2i therapy. These findings support its nephroprotective role beyond glycemic control.